The Effect of Boarding School and Learning Discipline Towards Economic Achievement of MA Al-Mawaddah Students (Universitas Negeri Semarang, 2023)
This research aims to determine the effect of boarding school and learning discipline on economic achievement of MA Al-Mawaddah students. This research classified as ex-post facto research with quantitative method. The population was students of MA Al-Mawaddah grades X, XI, and XII from social major. The sampling technique was proportionate random sampling with total sample 134 students. Data collection techniques was questionaries and documentation. The documentation taken from Economic grade of end-semester assessment. The validity test used Pearson Product Moment test and the reliability test used Cronbach Alpha test. The hypothesis tested with linear regression test. The results show that boarding school and learning discipline has positive and significant effect on economic achievement, it showed with Fcount>Ftable (15,901>3,06)